Randomized study FARVATER: Part II. Atorvastatin effects on endothelial function, vascular wall distensibility and stiffness - A. V. Susekov; T. A. Rozhkova; M. I. Tripoten’; O. A. Pogorelova; B. D. Kulev; T. V. Balakhonova; M. Yu. Zubareva; V. P. Masenko; A. N. Rogoza; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study atorvastatin (10 and 20 mg/d) effects on lipid, C-reactive protein, and fibrinogen levels, vascular wall structure and function in patients with coronary heart disease (CHD) and primary hyperlipidemia (PHL). Material and methods. In total, 50 CHD and PHL patients were randomized into two stable-dose atorvastatin groups (10 or 20 mg/d) for 24 weeks. Atorvastatin effects on lipid levels, endothelial function, vascular wall distensibility and stiffness, as well as treatment tolerability, were examined. Results. Twenty-four-week atorvastatin therapy (10 or 20 mg/d) reduced low-density lipoprotein cholesterol (LDL-CH) level by 34,9% and 43,9%, respectively (p<0,001). At baseline, vascular wall functional parameters did not differ significantly, reaching 7,2% and 6,4% for endothelium-dependent vasodilatation (EDVD), 21,3 and 18,7 10-3/kPa for vascular wall distensibility (DC) of common carotid artery (CCA); 8,0 and 9,1 Units for vascular wall stiffness (beta-index), respectively. Three-month therapy was associated with significant increase in EDVD – by 40,2% in 10 mg/d group, and by 51,3% in 20 mg/d group. After 24 weeks of the treatment, CCA distensibility increased by 45,3% (p<0,01) and 43,6% (p<0,01) in 10 and 20 mg/d groups, respectively. Vascular wall stiffness decreased by 23,4% (p=0,008) and 25,7% (p=0,002), respectively. There was no significant association between LDL-CH decrease and EDVD, distensibility or stiffness dynamics. During 24-week follow-up, 2 adverse events (4%), linked to atorvastatin therapy, were registered. Conclusion. In CHD and PHL patients, atorvastatin (10-20 mg/d) increased EDVD by 40-51%, CCA distensibility by 43-45%, reduced vascular wall stiffness by 23-26%, and was well tolerated.